Applying Service-Dominant Logic to Translation Service Provision - Kujamäki, Minna (HERMES - Journal of Language and Communication in Business, 2020)
Translation is commonly regarded as a service both in translation industry and within Translation Studies (TS), but the question of what makes translation a service has not been widely explored. This conceptual paper looks at non-literary translation as a service, applying a paradigm of Service-Dominant S-D logic (S-D logic) to the field. Practices in translation service provision are analysed using the Facilities-Transformation-Usage framework (FTU framework), designed on the premises of S-D logic, as a tool. The paper shows that translation practices in general comply with this theoretical perspective, making translation, by definition, a service, and opens a window into the aspects that make it a service. Some current practices in the field do not, however, meet the criteria of an ideal service. These practices are discussed briefly in order to pinpoint, from the service theoretical point of view, where the problems lie.